Commodities ambientais: um novo modelo de mercado interpretado à luz do conteúdo de bem ambiental - Venturini, Alessandro Fuentes (2010)
This issue discusses the consumption needs of the modern society, which comes from the transitory pleasure as well as from the rapid obsolence index reached by products and services, demonstrating that these levels of consumption, although they keep the economy growth and promote the development in poorer countries removing people from misery, are encouraging the use of natural resources in an unsustainable way. In this context, the present consumption may be used to preserve the environment and, at the same time, may promote development of the poorer countries by using a new market model based on environmental commodities. For that, a new interpretation of environmental property is necessary in order to allow that the environmental resources are extracted from nature, with the guarantee to all the citizens regarding the right of an environment ecologically balanced, right which may be used to build a new conception of environmental property